The Effect of Divergent Thinking Strategy on Functional Thinking And The Performance of Basketball Shooting Skills (Journal of the College of Basic Education, 2025)
This study aims to build a scale of career thinking to perform basketball skills for students, prepare educational exercises and employ them with vocabulary of ramified thinking strategy in practical physical education lesson, and to identify the impact of the strategy of complex thinking in career thinking and performing basketball correction skills, and there are statistically significant differences between the results of the remote tests of the experimental research and control groups in thinking Job and performance skills performance (free throw performance, shooting performance from jumping, peaceful correction performance) basketball, basketball,The experimental curriculum in designing the experimental and controlled groups has adopted (60) students from the second stage in the Department of Physical Education in Sports Science at the Faculty of Education/ Al -Farahidi University, for the academic year (2023/2024) representing (66.667 %) of this society, and a scale was built to thinking to perform basketball and employ the vocabulary of the strategy with educational exercises and their application in the practical basketball lesson, as all skills are allocated (4) educational units, which were studied at a rate of two lessons per week on Monday and Tuesday of each week, as the application of educational units (6) weeks continued, For the application to be in the main section of (75) minutes from the time of the practical basketball lesson of (90) minutes, and the search procedures continued for the period of time (7/3/2024) to (16/4/2024) and after the completion of the search experience Results (SPSS) has been addressed, To be the most important conclusions and recommendations that the measure of career thinking to perform basketball skills is suitable for students of the second stage at Al -Farahidi University, and it is suitable for what was prepared for it, and it has the foundations and scientific transactions for its transaction, and that the application of educational exercises with the vocabulary of the complex thinking strategy in practical lessons helps in improving the level of job thinking to perform Basketball skills, and helps to improve the performance of each of the correction skills (free throw performance, shooting from jumping, peaceful shooting performance) basketball for students who study with them, and by superiority over their peers who study without them, and it is necessary to increase the interest of the basketball school teachers By measuring job thinking to perform students aiming at students in order to provide support and support to students to improve the skill of basketball, it is necessary to increase interest in taking into account the individual differences when applying the complex thinking strategy and working on the multiplicity and diversification of educational situations and tasks in a way that meets the achievement of educational goals to teach the skill performance in basketball..